A comparative petrophysical evaluation of the Abu Roash, Bahariya, and Kharita reservoirs using well-logging data, East El-Fayoum, Egypt - Mohamed Osman Ebraheem; Hamza Ahmed Ibrahim; Ahmed Hosny Senosy (Scientific Reports)
Abstract The exploration and development of hydrocarbon resources in the Western Desert require more continuous activities. The Silah is a newly discovered field in this region. Therefore, this study emphasizes the application of petrophysical evaluation to sandstone and carbonate reservoirs from the late and early Cretaceous. These formations are the most potential hydrocarbon reservoirs in the studied area as a part of the western desert. Additionally, this study involves a comparative evaluation of the Abu Roash, Bahariya, and Kharita reservoirs using well-logging data by applying different cross-plots that are used for determining different petrophysical parameters such as shale volume, porosity, fluid saturation, permeability, and net-to-gross ratio. These logs are gamma-ray (GR), calliper, resistivity (RLA5, RLA3, and RXOZ), photoelectric effect (PEFZ), neutron (APLC), and density (RHOZ). These plots agree with the results deduced from the interpretation of lithologic logs. Fourteen hydrocarbon-bearing zones are identified in the Silah field. Only two zones, namely, Zone 2 in Silah-15 and Zone 1 in South Silah-1X, are considered the best for hydrocarbon generation. These zones are characterized by low to moderate shale volume, moderate to high total porosity, good effective porosity, low water saturation, and high net-to-gross ratio. These zones lie in the Abu Roash/F member. These deduced points prove that the Abu Roash/F member can be an abundant hydrocarbon reservoir. This member in the Silah field appears to be a promising hydrocarbon reservoir because it matches the petrophysical parameters of the investigated zones and others in the northwestern Desert. This suggests that there may be reservoir continuity and similarity.